Self–Regulation as an Antecedent of Academic Achievement: A Mixed Method Study (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study determined the antecedent role of self-regulation skills in the student's academic achievement. A descriptive research design using concurrent mixed methods was employed to determine the influence of self-regulation on the academic achievement of the students. A total of 382 Grade 11  senior high school students of a private school in Cagayan de Oro City were the respondents of the study. The findings of the study revealed that reflection stood out as having a significant influence on their academic achievement. Furthermore, the student's overall self–regulation skills significantly influence their academic achievement. Students with higher self-regulation, especially in the area of reflection, have higher academic achievements. Self-regulation skills of reflection, planning, time management, and monitoring have various degrees of impact on academic achievement. It is recommended that teachers should design lessons and activities that prompt the students to engage in meaningful self-reflection, which can foster deeper understanding and improved performance.